Digitalisasi koperasi : pengelolaan akun koperasi mahasiswa di market place - Wida Wulandari; Irwan Adimas Ganda Saputra; Putri Hestiningrum (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2023)
The Covid-19 pandemic has become one of the obstacles for student cooperatives at Surabaya State University in improving the economy. Turnover every year which continues to decline encourages administrators to immediately find solutions to problems that occur. The Community Service Program provides training in the field of digitizing student cooperatives at Surabaya State University, especially in increasing sales turnover through the marketplace, which has a significant impact. Administrators also carry out direct simulations to better understand the management of kopma account in the marketplace so that they can provide the best service for consumers and potential consumers in mthe wider community not limited to only Surabaya State University. Based on training and simulations that have been held, the questionnaire results show that the ease of managing KopmaUnesa account shows very manageable and the level of customer satisfaction based on the answers received shows very good.